Intranasal delivery of a Fas-blocking peptide attenuates Fas-mediated apoptosis in brain ischemia. Issue 1 (December 2018) - Ullah, Irfan; Chung, Kunho; Oh, Jungju; Beloor, Jagadish; Bae, Sumin; Lee, Sangah; Lee, Minhyung; Kumar, Priti; Lee, Sang-Kyung
Abstract Ischemic stroke-induced neuronal cell death results in the permanent disabling of brain function. Apoptotic mechanisms are thought to play a prominent role in neuronal injury and ample evidence implicates Fas signaling in mediating cell death. In this study, we describe the neuroprotective effects of a Fas-blocking peptide (FBP) that by obstructing Fas signaling in cerebral ischemia inhibits apoptosis. Using an intranasal administration route in a rat model of focal cerebral ischemia, we demonstrate that nose-to-brain delivery of FBP after middle cerebral artery occlusion (MCAO) surgery results in the delivery and retention of FBP in Fas-expressing ischemic areas of the brain. A single intranasal administration of 2 mg/kg FBP resulted in significantly reduced neuronal cell death by inhibiting Fas-mediated apoptosis leading to decreased infarct volumes, reduced neurologic deficit scores and recovery from cerebral ischemia. Intranasally delivered FBP might be a promising strategy for the treatment of cerebral ischemic stroke.